2000
DOI: 10.7326/0003-4819-133-9-200011070-00015
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis: New Insights. Part 2: Treatment Approaches

Abstract: Osteoarthritis is the most common form of arthritis, affecting millions of people in the United States. It is a complex disease whose etiology bridges biomechanics and biochemistry. Evidence is growing for the role of systemic factors, such as genetics, diet, estrogen use, and bone density, and local biomechanical factors, such as muscle weakness, obesity, and joint laxity. These risk factors are particularly important in the weight-bearing joints, and modifying them may help prevent osteoarthritis-related pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
287
0
19

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(308 citation statements)
references
References 90 publications
2
287
0
19
Order By: Relevance
“…Importantly, although potential treatments available for medial knee osteoarthritis are increasing, only a limited number have proven to be effective (7). Despite previous reviews that are generally supportive of valgus bracing and highlight their relatively low cost and associated risks (11,(52)(53)(54), the rates of valgus brace prescription are very low (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, although potential treatments available for medial knee osteoarthritis are increasing, only a limited number have proven to be effective (7). Despite previous reviews that are generally supportive of valgus bracing and highlight their relatively low cost and associated risks (11,(52)(53)(54), the rates of valgus brace prescription are very low (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that multiple clinical trials have shown that PA and exercise are beneficial for people with arthritis, almost one-third of persons with arthritis are completely inactive, and only one-quarter get enough PA to comply with national PA recommendations (13)(14)(15)(16)). Yet, it is possible for persons with arthritis to meet the national recommendations by engaging in moderate types of joint friendly PA such as walking, gardening, bicycling, and swimming.…”
Section: Discussionmentioning
confidence: 99%
“…Because arthritis is the leading cause of disability, one benefit of increasing PA levels may be decreasing the development of arthritis-related disability (17). Evidence from randomized clinical trials suggests that PA, both aerobic and resistive exercise, benefits persons with knee osteoarthritis, contributing to modest improvements in disability, physical performance, and pain (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Currently there exists no accepted medical treatment with structure or disease modification in OA (24)(25)(26)(27)(28)(29)(30)(31), despite the high and vastly increasing number of patients with a need to be treated. In this context, quantitative MRI can help to identify promising drug targets (by identifying tissue components that change first and are responsible for changes in other tissues) and, in particular, to monitor structural effects of drugs in order to prove their effectiveness.…”
Section: Rationale For Quantitative Mri Of Cartilage and Bone In Ostementioning
confidence: 99%